Exploring On-Campus Student Satisfaction on Learning Via Mooc - Muhammad Haziq, Bin Roslan; Chen, Chwen Jen (Human Resource Management Academic Research Society, 2021)
Satisfaction is the key to determine students’ intention to continue using a Massive Open Online Course (MOOC) and examining these students’ MOOC learning experience can provide insights into their satisfaction. Thus, this study aims to explore the MOOC learning experience of on-campus students who took up a MOOC on ICT Competency to identify aspects that are satisfying as well as dissatisfying to them. This study employed a qualitative approach in which eight students who had completed the ICT Competency MOOC were purposively chosen. The critical incident technique (CIT) was employed to collect and analyze information about significant experiences or critical occurrences of these participants during their MOOC learning. The meanings to these critical occurrences were collected to determine whether each experience inferred satisfaction towards the MOOC learning experience or otherwise. Participants were interviewed individually and the interview was guided by the eight aspects of Badrul Khan’s e-learning framework. The study reveals six satisfaction factors and another six dissatisfaction factors that point to six important lessons in designing and implementing a MOOC. The six lessons learned include the importance of providing flexibility in learning; providing a user-friendly interface and appealing as well as comprehendible learning materials; providing manageable, relevant assessments with clear assessment instructions; providing adequate instructor engagement; providing essential infrastructure and stable technological affordances; and incorporating anti-plagiarism strategies.